PENGARUH SUSTAINABILITY REPORT TERHADAP NILAI PERUSAHAAN (Studi Perusahaan Non Keuangan dari tahun 2018-2020) Proxy : PBV (Price to Book Value) - Arga Surya Wira; Dwi Urip Wardoyo; M. Luthfi Islahuddin; Rahmania Gita Safitri; Syifa Nabbilah Putri (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of Sustainability Reporting on Firm Value. The population of this study are non-financial companies from 2018-2020. The sampling method used in this research is purposive sampling method with predetermined criteria so as to produce 138 samples of non-financial companies to be studied. The data used are secondary data in the form of financial reports and company annual reports obtained through the website www.idx.co.id. The results of this study show that the Sustainability Report has a positive and significant effect on firm value